Аnalysis of the geological characteristics of aluminum deposits in Ukraine - Batrak O.S.; Dereviahina N.I. (НТУ "ДП", 2025)
Aluminum is one of the most widespread elements in the Earth’s crust, being a component of over two hundred minerals; however, only a few of them have industrial significance. The main sources of aluminum raw materials are bauxites, nepheline ores, kaolins, and alunite rocks. Ukraine possesses significant reserves of these resources, which makes the study of their geological structure, distribution, and occurrence conditions an important aspect. The largest aluminum reserves are found in residual and re-deposited weathering crusts of acidic, alkaline, and basic rocks. In Ukraine, the main forms in which aluminum occurs are bauxites, nephelines, alunites, and kaolinites. Bauxites are represented by relatively small explored reserves, concentrated in the Smila, Vysokopillia, and Nikopol deposits, located within the weathering crusts of Precambrian formations. Bauxites are also found in the Pryazovia region and the Carpathians.
Keywords: алюміній; видобування алюмінію; родовища алюмінію